O programa estadual para a diversidade numa perspectiva inclusiva no município de Quirinópolis-GO : princípios, ações e percepções - Kamimura, Ana Lúcia Martins (2006)
This research seeks to understand the principles, actions and perceptions present in the State Program for Diversity in an Inclusive Perspective in the municipal district of Quirinópolis - GO. For such we inquired about the politics of inclusive education in force and we went through the works of some authors in the attempt to understand the aspects concerning inclusion and exclusion, with our mind fixed on education, as well as the rationality of the educational politics of inclusion and the rationality/subjectivity of the individuals involved in the educational process. In the light of this we observed, described and analyzed the perceptions of the individuals with regard to the effective implementation and applicability of the above mentioned program. Nine interviewees participated in this study, three being managers, three teachers and three members of the inclusion support team. These individuals are directly linked to the Sub-secretariat of Education, the organ which is responsible for the State in the municipal district of Quirinópolis - GO. The objective was to identify the rationalities of the state politics of inclusion in Goiás through the analysis of the rationalities/subjectivities of the individuals involved in the State Program for Diversity in an Inclusive Perspective developed in the school context of the municipal district of Quirinópolis, based on the suppositions of an education that has as its principle respect for differences. For this purpose, we used as a methodological outline the qualitative research modality, which obeyed the following methodological steps: bibliographical research, documental research and semi-structured interviews. We identified in the analysis of the data obtained from the interviews some categories: the question of inclusion/exclusion, innovations, changes and modernization; the question of sensibility, involvement and personal and professional responsibility; the question of expectations. In the light of these inquiries we considered that the perception of the great majority of the individuals obeys the logic traced by the principles and the actions determined by the State Program for Diversity in an Inclusive Perspective in the municipal district of Quirinópolis - GO, in spite of in some moments presenting certain discomfort due to the reality lived in the daily life of the school. However, this does not render and did not render the environment less excluding than it was already, in other words, the offer of educational services still takes place in an environment where there are restrictive actions with regard to differences.